The Southern Tip of the Electroacoustic Tradition - Dal Farra, Ricardo (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2007)
Music and electronic technologies were matching forces a long time ago in Latin America. Many composers from different countries of the region were attracted by the new possibilities that the tape recording at first, then the voltage-controlled synthesizer and the computers, were offering. This article includes excerpts from interviews to composers César Bolaños from Peru, Alberto Villalpando from Bolivia and Manuel Enríquez from Mexico. They were selected to offer the reader an approach to the work and thinking of some widely recognized Latin American composers whose artistic production included electroacoustic music during the pioneering year